Online recruitment for organizational knowledge management: a quantitative study - Silva, Susana (2017)
The process of Recruitment and Selection of new employees has a growing influence on business results and, nowadays, the use of knowledge and information and communication technologies enables this process to be faster and more complete. The need to improve the existing resources in companies has conditioned the changes in the Recruitment and Selection process and, over time, we observe the transformation of this process. Thus, Recruitment and Selection became a strategic process in Human Resources Management improving the organization's competitiveness. The objective of the study is to understand the role of online recruitment for organizational knowledge management; and to characterize the most used social networks in Online Recruitment, identifying the main reasons to use online recruitment during the process of recruitment and selection. ln this quantitative study, 112 companies fulfilled a questionnaire that evaluated the online recruitment process. The main results suggested that national companies and companies with more than 250 employees use more online recruitment. The fact that some companies have job openings available on multiple websites simultaneously, making information available 24 hours a day, reducing the time and process costs and streamline communication between candidates and the organization are some of the most listed reasons to use the Online Recruitment. Otherwise, the use of traditional methods of recruitment and the fact that the access to social networks are not allowed in some organisations are some of the reasons cited for not using this method of recruitment. Thus, it can be concluded that the Information and Communication Technologies are present in the process of recruitment and selection and that this is a reality existing in organizations as a tool to support of knowledge management.